Antioxidant and hypoglycemic activities of extract and fractions of Rambutan seeds (Nephelium lappaceum L.) - Slyvia Soeng (Biomedical Engineering, 2015)
Objective : This research was done to measure the antioxidants and hypoglycemic activities of NLS extract andfractions.Methods: The ethanol extract of rambutan seeds were prepared by maseration method and the fractions (nhexane,ethyl acetate, buthanol and water) by separation of extract based on the polarity. The antioxidantactivity was determined by using superoxide dismutase value (SOD), 1,1-diphenyl-2-picryl-hydrazyl (DPPH)radical scavenging activity. The hypoglycemic activity was determined by using inhibition of α-glucosidase test.The DPPH scavenging and hypoglycemic activities were analized by median of Inhibitory Concentration (IC-50).Result : The highest SOD activity showed that ethyl acetate and aqueous fraction of NLS were 3.3771 μg/ml and3.0374 μg/ml. Meanwhile DPPH assay showed that both NLS extract and fractions had low DPPH scavengingactivity. Hypoglycemic activity showed that extract of NLS had highest activity as α-glucosidase inhibitor.Conclusion : NLS extract and fractions have high SOD antioxidant value but low DPPH scavenging activity andcan be used as potential hypoglycemic agent.